The Impact of Community-Based Digital Literacy Training to Support the Merdeka Belajar Program - Imron Imron; Suwito Eko Pramono; Ani Rusilowati; Sulhadi Sulhadi (International Conference on Science, Education, and Technology, 2023)
The implementation of the Merdeka Curriculum as one part of the Merdeka Belajar program is a must and requires support from various sides. Among them is strengthening digital literacy, which is inseparable from fostering a culture of literacy. This research aims to determine the motivation of teachers to participate in digital literacy training and the completeness of participants in terms of those who take part in further training until the end of the activity. In addition, it can find out literacy's understanding of digital literacy. The methodology used was research and development with data collection techniques of documentation, observation, and questionnaires. A total of 1,130 participants self-registered online and attended the opening. A total of 677 participants continued the training activities both online and offline. Participants were divided into 28 classes, consisting of 26 online classes and 2 offline classes. After attending the advanced training for 3 days, 584 participants passed. The community-based training model is very useful to facilitate the improvement of teacher competencies, especially in the field of digital literacy, voluntarily and free of charge. Respondents consisted of 44 male participants and 155 female participants. In addition, the online model had 162 participants, the offline model had 10 participants, and the offline and online models had 27 participants. As a result, general literacy understanding reached 83%, knowledge of types of literacy 84%, literacy competence 84%, knowledge of the school literacy movement 84%, the importance of literacy 85%, literacy habituation 82%, literacy integration 81%, and digital literacy knowledge 84%.